2011
DOI: 10.12968/bjon.2011.20.10.615
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices in the provision of nutritional care

Abstract: The nutritional care of patients is one of the primary responsibilities of all registered nurses (Persenius et al, 2008). A poor nutritional status can lead to malnutrition, which can have serious consequences for an individual's quality of life (Field and Smith, 2008). This paper commences with an introduction to the concept of nutrition, provides an overview of nutritional guidelines and nutritional screening tools which identify those at risk of malnutrition. It reviews the literature on nurses' knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 21 publications
1
15
0
9
Order By: Relevance
“…The authors showed a prevalence of malnutrition as high as 31.9% and stated that little has changed since the publication of research conducted by the European Council in 1999 (Beck et al, 2002). A review by Fletcher and Carey (2011) drew similar conclusions. Assessment of nutritional status, which is the very first strategy for identifying patients either malnourished or at risk (Green & James, 2013), is often not performed (Adams, Bowie, Simmance, Murray, & Crowe, 2008;Bavelaar, Otter, van Bodegraven, Thijs, & van Bokhorst-de van der Schueren, 2008;Kondrup et al, 2002;Lazarus & Hamlyn, 2005;Mowe et al, 2008;Persenius, Hall-Lord, B a ath, & Larsson, 2008;Suominen, Sandelin, Soini, & Pitkala, 2009).…”
Section: Introductionmentioning
confidence: 83%
“…The authors showed a prevalence of malnutrition as high as 31.9% and stated that little has changed since the publication of research conducted by the European Council in 1999 (Beck et al, 2002). A review by Fletcher and Carey (2011) drew similar conclusions. Assessment of nutritional status, which is the very first strategy for identifying patients either malnourished or at risk (Green & James, 2013), is often not performed (Adams, Bowie, Simmance, Murray, & Crowe, 2008;Bavelaar, Otter, van Bodegraven, Thijs, & van Bokhorst-de van der Schueren, 2008;Kondrup et al, 2002;Lazarus & Hamlyn, 2005;Mowe et al, 2008;Persenius, Hall-Lord, B a ath, & Larsson, 2008;Suominen, Sandelin, Soini, & Pitkala, 2009).…”
Section: Introductionmentioning
confidence: 83%
“…Such negative attitudes were expressed during group discussion when they were asked to give opinion on nutrition knowledge in their professional training. Different studies have revealed that in-service nutrition training can help to improve health workers' nutrition knowledge [18,19]. This may facilitate positive changes in their attitudes toward nutrition care and thus in their behaviour [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, health workers produced from teaching institutions have lacked adequate nutrition knowledge (3, 6). Such health workers may also lack the competence and skills to provide basic nutrition advice to their clients (2, 11). This incompetence, in turn, may be a factor deterring health workers from providing nutrition advice and management to their clients (12).…”
Section: Introductionmentioning
confidence: 99%